2013
DOI: 10.1007/s12029-013-9533-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Vitamin D Levels and Colonic Carcinomatous Polyps

Abstract: Vitamin D levels, using two established cutoffs, are not significantly associated with increased odds of membership in the CP+ group. However, our data suggest a possible threshold effect of vitamin D at <30 ng/ml associated with increasing odds of being CP+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Vitamin D exerts several biological effects other than the wellknown regulation of calcium and phosphorus metabolism: it has a role in activating innate and adaptive immunity (15,16) thus having a potential role in preventing infection, and it is also able to influence neo-angiogenesis (17,18) and pathways of apoptosis (19,20). Accumulating evidence has shown that vitamin D deficiency is associated with a higher risk of developing different types of cancer (21)(22)(23) and it may, thus, have a role in the diagnosis of HCC, together with other markers already known to be useful in the diagnosis of such neoplasia [e.g. alphafetoprotein (AFP), protein induced by vitamin K absence-II and their combination] (24).…”
mentioning
confidence: 99%
“…Vitamin D exerts several biological effects other than the wellknown regulation of calcium and phosphorus metabolism: it has a role in activating innate and adaptive immunity (15,16) thus having a potential role in preventing infection, and it is also able to influence neo-angiogenesis (17,18) and pathways of apoptosis (19,20). Accumulating evidence has shown that vitamin D deficiency is associated with a higher risk of developing different types of cancer (21)(22)(23) and it may, thus, have a role in the diagnosis of HCC, together with other markers already known to be useful in the diagnosis of such neoplasia [e.g. alphafetoprotein (AFP), protein induced by vitamin K absence-II and their combination] (24).…”
mentioning
confidence: 99%
“…Adams et al [27] suggested that the established inverse association between circulating VD and colonic adenoma may not apply to hyperplastic polyps. However, Sy and Bautista [28] pointed out a possible threshold effect of 25(OH)VitD 3 at < 30 ng/ml associated with increasing odds of being colonic polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in western countries have demonstrated the protective role of vitamin D for CRPs and CRC [ 13 ]. However, other studies have also proposed that vitamin D is not related to CRC [ 14 , 15 ]. One study even reported that Ca and vitamin D supplementation may increase the risk of sessile serrated adenomas or polyps [ 16 ].…”
Section: Introductionmentioning
confidence: 99%